Modified Zeolite with Transition Metals Cu and Fe for Removal of Methylene Blue from Aqueous Medium: Mass Spectrometry Study - João Henrique Lopes; Francisco Guilherme E. Nogueira; Maraísa Gonçalves; Luiz Carlos Oliveira (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
Textile industries are one of the main sources of water pollution. Wastewater containing dyes present a serious environmental problem because of its high toxicity and possible accumulation in the environ- ment. In this work were explored the characteristics of removal of methylene blue dye employing zeo- lites modified with transition metals (Cu, Fe). The zeolites with iron or copper were prepared by using NaY and Naβ zeolites as precursors, replacing part of ion sodium for copper or iron ions through the ion exchange method. All materials were characterized by several analytical techniques, in order to gain information about the structure and catalytic activity. Modified zeolites showed a remarkable ac- tivity in H2O2 decomposition and in the discoloration an organic dye in aqueous medium. ESI-MS stud- ies of the methylene blue oxidation showed that the oxidation of the dye occurs via a Fenton type sys- tem in which *OH radicals are formed in situ and added to the ring structure of the organic substrate. In addition, modification of the zeolite with transition metal proved to be an interesting pathway to produce efficient catalysts for the oxidation of organic molecules, i.e. dyes in aqueous media. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).